Peran Kepala Sekolah dalam Mengevaluasi Program Membaca Al-Qur’an dengan Metode Batiq Izzati di RA Al-Izzah Kota Serang - Fithoturrohmah Fithoturrohmah; Umayah Umayah; Wulan Fauzia (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze the role of the principal in evaluating the Qur’an reading program using the Batiq Izzati method at RA Al-Izzah in Serang City. The principal holds a strategic responsibility in ensuring the quality of education, including the implementation of religious programs that play a crucial role in shaping Islamic character in early childhood. The Batiq Izzati method is an internally developed approach by the Al-Izzah Foundation, designed to facilitate Qur’an reading through a gradual, enjoyable, and child-friendly method. This research employs a descriptive qualitative approach, using data collection techniques such as observation, interviews, and documentation. The findings indicate that the principal has fulfilled eight key leadership roles; however, the evaluation process is not yet optimal due to limited time and insufficient parental involvement. Evaluations are conducted daily by teachers and periodically by the principal to determine students' progress through different levels (jilid). Supporting factors include competent teachers, adequate facilities, and a structured evaluation system, while inhibiting factors involve time constraints and limited human resources. This study recommends strengthening the principal's role in continuous evaluation and fostering better collaboration between the school and parents to enhance the program's effectiveness.